Anacardato de cálcio como fonte de ácido anacárdico na alimentação de codornas japonesas em postura - Santos, Rebeca Cruz dos (2014)
The aim of the study was to evaluate the effects of adding calcium anacardate as source of anacardic acid in Japanese laying quails diets on performance and egg quality parameters. A total of 252 Japanese laying quails with 22 weeks of age were used, distributed in completely randomized design, with six treatments and six replications of seven broilers each. The treatments used were: T1 - diet without growth promoter (PC); T2 - diet with growth promoter; T3, T4, T5 and T6 - diets without growth promoter and addition of 0,25; 0,50; 0,75 and 1,0% of calcium anacardate (AC), respectively. The treatments did not affect feed intake, laying percentage, egg weight, egg mass, feed conversion and quality of the eggs: yolk, albumen and shell percentage, Haugh unit, specific gravity, shell thickness and yolk color. The calcium anacardate as source of anacardic acid, when added up to 1% in the diet, does not affect the performance and quality of the eggs of Japanese laying quails.